The Validity of Carotid Doppler Peak Velocity and Inferior Vena Cava Collapsibility Index in Identifying the Fluid Responders in Mechanically Ventilated Septic Shock Patients - Soliman, Mohamed; Magdi, Ahmed; Fatthy, Moataz; El-Sherif, Rania (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Measures of carotid artery flow or inferior vena cava diameter were recently shown to predict fluid responsiveness. Both are relatively superficial large vessels which can provide straightforward ultrasound evaluation & high-qualityimages.Methods: Our study is a prospective observational study on 30 mechanically ventilated septic shock patients in ICUto assess the fluid responsivenessby measuring carotid Doppler peak velocity&respiratory variation in inferior vena cava diameter against the increase in the cardiac index by echocardiographic calculations as a reference. All patients were given a fluid bolus 7 ml/ Kg crystalloid solution within 30 minutes, static and dynamic indices which include CVP, MAP, pulse pressure, difference between diameter of IVC during inspiration and expiration (ΔIVC- d) & carotid Doppler peak velocity in a single respiratory cycle (ΔCDPV) were measured before (T0) & after (T1). Vasoactive drugs infusion rate and ventilation settings did not changed during follow up. Patients were categorized either fluid responders “R” or non-responders “NR” according to an increase in cardiac output “CO” (increase in CO > 15 %.Results: Comparing responders & Non responders group we found a significant difference in Cardiac output measures,MAP & Δ CDPV pre & post fluid boluses as (5.26±4.42 L/min Vs. 10.62±5.73 L/min, 69.48±9.70 mmHg Vs. 84.90±10.36 mmHg&24.43±11.87%Vs33.22±11.00%) respectively with P-value (0.007, 0.05&0.01) respectively, on the other side , ΔD-IVC & Δ CVP pre & post fluid boluses didn’t show any statistical difference as (11.91±9.41 % Vs. 13.51±9.56 %, 5.86±5.22 cmH2O Vs 7.22±4.82 cmH2O) with P-value (0.87&0.68)respectively.Δ CDPV increase in response to increased intravascular volume in R group showed sensitivity 81%, specificity 66.7%. APACHE II, SOFA day 0,5 didn’t showed any difference between the R & NR group (16.05±3.23 Vs 18.44±3.81, 11.48±2.82Vs12.11±2.80& 12.95±3.68Vs12.56±3.97) respectively with P-value (0.164, 0.625 & 0.79) respectively. Conclusion: ΔCDPV was a more precise & even easier assessment tool with better sensitivity and specificity for evaluation of fluid responsiveness than the ΔD-IVC in patients with septic shock upon mechanicalventilation. Also, ΔCDPV has a high correlation with SVI increasing parameters assessed by echocardiography after fluid boluses. On the other hand and in comparison, CVP showed low accuracy in predicting fluid responsiveness.